63Cu(n, α)60Co cross sections in the MeV region. (2nd March 2023) - Liu, Jie; Cui, Zengqi; Hu, Yiwei; Bai, Haofan; Yang, Yi; Ruan, Xichao; Xia, Cong; Chen, Jinxiang; Zhang, Guohui; Gledenov, Yu M; Sansarbayar, E; Khuukhenkhuu, G; et al.
Abstract: Cross sections of the 63 Cu( n, α ) 60 Co reaction in the MeV neutron energy region were measured using both the direct measurement method and the activation method. A twin-gridded ionization chamber was used for the direct measurement while the high-purity germanium detector was used for the activation method. The measured cross sections using the two methods are consistent within measurement uncertainties. The present results support the evaluation data in the ENDF/B-VII.1 library instead of the latest evaluation data in the ENDF/B-VIII.0 library, which is helpful to clarify discrepancies in measurement and evaluation data. TALYS-1.9 code analysis was performed which shows that the measurement cross sections can be well reproduced with minor adjustments of the input parameters. Through the calculation, it is found that the compound mechanism predominates the 63 Cu( n, α ) 60 Co reaction with ratios higher than 0.7 for neutron energy less than 20 MeV.